1997
DOI: 10.1111/j.1751-5823.1997.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The Creation of the Office for National Statistics

Abstract: A new Office for National Statistics was created in the United Kingdom in 19% following a series of developments designed to strengthen the relevance and integrity of statistics. This paper describes these fundamental changes and sets out a blueprint for future progress. It also sets current developments in the United Kingdom in an historical and international context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Interestingly, anxiety about the quality of data produced, far more than ideology, has driven the overhaul of Britain's statistical system over the past 20 years. After several government reviews questioned the quality of the statistics being produced by Government Statistical Service (GSS), and the Royal Statistical Society (1990) noted that there was a serious erosion of public confidence in UK official statistics, the government centralized responsibility for statistics in a new Office for National Statistics (ONS) in 1996 (Pullinger 1997). Since this development the British government has furthered its pursuit of an autonomous statistical agency.…”
Section: Lessons From Abroadmentioning
confidence: 99%
“…Interestingly, anxiety about the quality of data produced, far more than ideology, has driven the overhaul of Britain's statistical system over the past 20 years. After several government reviews questioned the quality of the statistics being produced by Government Statistical Service (GSS), and the Royal Statistical Society (1990) noted that there was a serious erosion of public confidence in UK official statistics, the government centralized responsibility for statistics in a new Office for National Statistics (ONS) in 1996 (Pullinger 1997). Since this development the British government has furthered its pursuit of an autonomous statistical agency.…”
Section: Lessons From Abroadmentioning
confidence: 99%
“…Although institutionalised older adults have been shown to be at high risk of malnutrition (2) , previous research has shown that, even among independent older people, 3 % of men and 6 % of women are underweight (3) . With the proportion of the UK population that is over 75 years of age likely to double in the next 40 years (4) , and 10 % of the UK free-living older population classified as underweight (5) , screening for nutritional status should be undertaken routinely in elderly patients living at home to determine their risk of malnutrition (6) . The aim of this study was to determine the nutritional status, dietary variety and factors affecting satisfaction with food-related quality of life in older people living in their own homes.…”
mentioning
confidence: 99%